Brevi note di coroplastica siracusana: due esemplari di statuette con bambino - Angela Maria Manenti (Les Carnets de l’ACoSt)
Two mold-made, terracotta figurines representing a woman holding a child are rare within the coroplastic typology of Syracuse. Although they were brought to light during earlier excavations in Syracuse they have never been the object of study. Their typology may reference female cults in the fifth and fourth centuries B.C.E.